Study on the calculation method of seismic coefficient for slope stability using shear beam theory - Mengchen WANG; Yahong DENG; Huandong MU; Nan YANG; Faqiao QIAN (Zhongguo dizhi zaihai yu fangzhi xuebao)
Pseudo-static method is a common used approach to evaluate the seismic stability of slopes, where the choice of seismic coefficients directly affects the accuracy of the evaluation. Therefore, thoroughly exploring the determination methods and values of seismic coefficients in the quasi-static method is of great significant both theoretically and in engineering practice. Based on shear beam theory, this paper derives the formula for the seismic response acceleration for rectangular trapezoidal slopes and analyzes the impact of various factors on slope response acceleration. Recommended seismic coefficients under different seismic intensities were determined as follows: 0.04 for Intensity Ⅵ, 0.07 for Intensity Ⅶ, 0.11 for Intensity Ⅷ, and 0.21 for Intensity Ⅸ. The research results reflect the dynamic response characteristics of slopes and provide scientific theoretical support for the selection of seismic coefficients.